SOA-based framework for home and building automation systems (HBAS) - Perumal, Thinagaran; Ramli, Abdul Rahman; Chui, Yew Leong (Science & Engineering Research Support Society, 2014)
Home and building automation systems (HBAS) today are categorized by plethora of data formats, communication platforms and software services accessible via heterogeneous embedded devices. These heterogeneous embedded devices characterized a building into a data intensive entity, generating numerous data and complex control information, brings a much heavy load to the HBAS. Consequently, this leads to interoperation difficulties among those devices for information exchange and operation management. In this paper, a Service Oriented Architecture (SOA) based framework that leveraged by services is proposed to manage HBAS efficiently by reducing their workload during joint execution of tasks. The proposed framework consists of several layers dedicated for services interwoven by Event-Condition-Action (ECA) oriented decision mechanism for managing heterogeneous embedded devices. The proposed framework is viable and highly efficient to be deployed for HBAS with limited computing resources.